Kemampuan Representasi Matematis Siswa pada Pembelajaran Berbasis Teori Van Hiele di Materi Segiempat Kelas VII SMP Negeri 1 Indralaya Utara - Armadan Armadan; Somakim Somakim; Indaryanti Indaryanti (Jurnal Elemen, 2017)
This research belongs to description quantitative research which aimed to find out the description of students’ ability of the mathematical representation by using Van Hiele Theory based learning on rectangular material. The subjects of this research are 27 students of VIIA grades at SMP N 1 Indralaya Utara. The technique collecting data was done by using test method and observation. Test Instrument which is used is two essays. Observation is used to look at student learning activities based on Teori Van Hiele and for supporting the test result of students’ mathematical representation skill. The research result showed that students’ mathematical representation skill on VIIA grade of SMP N 1 Indralaya Utara is categorized well enough, with the following details: the precentage of students mathematical representation skill which is very nigh about 7,41%, for nigh category is about 55,56%, for medium category which is about 33,33% and for low category is about 3,7%. The precentage of students’ mathematical representatation which is able to present 0 level of Van Hiele Theory with visual representation about 100%, the percentage of students who are able to present 1 level of Van Hiele Theory with verbal representation about 74,07%, mean while 2 level with verbal representation and simbolic representation serially about 22,22% and 37,03%.